One-pot Ugi-azide and Heck reactions for the synthesis of heterocyclic systems containing tetrazole and 1,2,3,4-tetrahydroisoquinoline - Jiawei Niu; Yuhui Wang; Shenghu Yan; Yue Zhang; Xiaoming Ma; Qiang Zhang; Wei Zhang (Beilstein Journal of Organic Chemistry, 2024)
A new method for the synthesis of heterocyclic systems containing tetrazole and tetrahydroisoquinoline is developed via the performance of one-pot Ugi-azide and Heck cyclization reactions. The integration of the multicomponent and post-condensation reactions in one-pot maximizes the pot-, atom-, and step-economy (PASE).